Microbiological quality of mines frescal cheese - Pinto, Natany Dutra (2020)
The objective of this study was to evaluate the presence of microorganisms harmful to human health, contaminants of Minas Frescal cheeses, sold in commercial establishments in the municipality of Rolim de Moura - RO. For this, a descriptive research was done, which through description, analysis and quantitative verification, there was knowledge of the number of microorganisms located in the cheese samples. Thirty samples of Minas Frescal cheese marketed in the municipality of Rolim de Moura were evaluated, resulting in three positive samples for coliforms at 45 ° C, 13 positive samples for Escherichia coli, and all 30 positive samples for Staphylococcus sp., Through this analysis microbiological analysis it was found that the quality of Minas Frescal cheese consumed by the Rolimourense population is not within the ideal standards, related to contamination, which can cause public health problems.